Estudo estrutural de compostos de manganês contendo ligantes bidentados - Souza, Jonathan Augusto Matioli de (2023)
Manganese is currently the 4th most used metal on Earth in terms of tonnage, and is mined in over 30 countries, generating millions of jobs and billions of dollars in taxes. It presents an extremely wide chemistry, being able to adopt different oxidation states, allowing its complexes to present a range of possible applications. Furthermore, it is not only vital for human health, but for life in general, and its lack can potentially endanger human health. The oxidation state II of manganese is the most thoroughly studied state, being in aqueous solution the most stable state by far. As for the oxidation state III, almost all complexes are octahedral and of high spin, thus presenting a valence shell equal to 3d4, presenting the eg orbital unevenly occupied, causing a distortion in the structure by the Jahn-Teller effect. Studies involving Catechol as a ligand have been growing over the years. This is due to the fact that Catechol is classified as a non-innocent ligand, that is, a ligand in a metallic complex where the oxidation state is not clear, related to its role and influence on the final electronic distribution of certain complexes. In this way, both the final oxidation state and the internal electronic distribution can be modulated, making it a great object of study both by theoretical and experimental means. Thus, the present work aims at the synthesis, characterization and theoretical study of manganese complexes coordinated by the catechol ligand. Initially, the synthesis of the cis-[Mn(bpy)2Cl2] complex was performed, with bpy = 2,2'-bipyridine, a complex already known and described in the literature, but which served as a point of study for optimization and computational calculations using as methods the Density Functional Theory (DFT) and the Time-Dependent Density Functional Theory (TDDFT), which were applied to the complex Na[Mn(cat)Cl2], where cat = catechol. All the synthesized complexes were characterized through spectroscopic techniques in the infrared region where characteristic stretches for the complexes could be observed and, subsequently, through the spectrometry technique in the ultraviolet-visible region it was possible to observe the characteristic bands for both the ligands and for the complexes. Conductometric and elemental analysis techniques were also applied for both complexes and cyclic voltammetry techniques for the Na[Mn(cat)Cl2] complex. Finally, the calculations of DFT and TD-DFT allowed to elucidate the transitions observed experimentally in the ultraviolet and visible region of the synthesized complexes, making it possible to calculate the NTOs (Natural Transition Orbitals) of the complexes, a method capable of separately performing the unitary transformation for occupied and virtual molecular orbitals, so that only one or very few pairs of orbitals have dominant contributions.